Effect and mechanism of nano-materials on plant resistance to cadmium toxicity: A review - Jiyuan Yan; Xiuzhe Wu; Tong Li; Weiru Fan; Mohamed Abbas; Mengzhan Qin; Runze Li; Zhiguo Liu; Peng Liu (Ecotoxicology and Environmental Safety, 2023)
Cadmium (Cd), one of the most toxic heavy metals, has been extensively studied by environmental scientists because of its detrimental effects on plants, animals, and humans. Increased industrial activity has led to environmental contamination with Cd. Cadmium can enter the food chain and pose a potential human health risk. Therefore, reducing the accumulation of Cd in plant species and enhancing their detoxification abilities are crucial for remediating heavy metal pollution in contaminated areas. One innovative technique is nano-phytoremediation, which employs nanomaterials ranging from 1 to 100 nm in size to mitigate the accumulation and detrimental effects of Cd on plants. Although extensive research has been conducted on using nanomaterials to mitigate Cd toxicity in plants, it is important to note that the mechanism of action varies depending on factors such as plant species, level of Cd concentration, and type of nanomaterials employed. This review aimed to consolidate and organize existing data, providing a comprehensive overview of the effects and mechanisms of nanomaterials in enhancing plant resistance to Cd. In particular, its deep excavation the mechanisms of detoxification heavy metals of nanomaterials by plants, including regulating Cd uptake and distribution, enhancing antioxidant capacity, regulating gene expression, and regulating physiological metabolism. In addition, this study provides insights into future research directions in this field.